Killing of Serratia marcescens biofilms with chloramphenicol - Christopher Ray; Anukul T. Shenoy; Carlos J. Orihuela; Norberto González-Juarbe (Annals of Clinical Microbiology and Antimicrobials, 2017)
Abstract Serratia marcescens is a Gram-negative bacterium with proven resistance to multiple antibiotics and causative of catheter-associated infections. Bacterial colonization of catheters mainly involves the formation of biofilm. The objectives of this study were to explore the susceptibility of S. marcescens biofilms to high doses of common antibiotics and non-antimicrobial agents. Biofilms formed by a clinical isolate of S. marcescens were treated with ceftriaxone, kanamycin, gentamicin, and chloramphenicol at doses corresponding to 10, 100 and 1000 times their planktonic minimum inhibitory concentration. In addition, biofilms were also treated with chemical compounds such as polysorbate-80 and ursolic acid. S. marcescens demonstrated susceptibility to ceftriaxone, kanamycin, gentamicin, and chloramphenicol in its planktonic form, however, only chloramphenicol reduced both biofilm biomass and biofilm viability. Polysorbate-80 and ursolic acid had minimal to no effect on either planktonic and biofilm grown S. marcescens. Our results suggest that supratherapeutic doses of chloramphenicol can be used effectively against established S. marcescens biofilms.